The Impact of Environmental Regulation on Technological Innovation - Qi, Ming (Université d'Ottawa | University of Ottawa, 2013)
This paper reviews the existing theoretical and empirical literature on the relationship between environmental regulation and technological innovation. The paper begins with a review of the most commonly used environmental policies, and then specifies the motivation of technological innovation led by environmental regulations by reviewing several key theoretical and empirical studies. Following this discussion, the paper explains how conventional and evolutionary regulation instruments affect technological innovation in different industrial sectors. In this section, a significant trend, which reveals how the central role of governmental regulation in motivating environmental innovation has begun to weaken in recent years due to the emergence of new motivations from inside and outside the industry, is explored. The next section examines two industrial sectors in terms of the current regulatory policies and regulatory trends. In the last section of the paper, I review several recent studies, which analyze the new role environmental regulation plays in innovation. The aim of this section is to explain why some firms are willing to engage in costly R&D investment to exceed environmental regulations. To conclude, this paper will provide the reader with a clear understanding of the relationship between environmental regulation and innovation.